2011
DOI: 10.4103/0975-7406.80779
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic activity of medium-polar extract from the leaves of Stevia rebaudiana Bert. (Bertoni) on alloxan-induced diabetic rats

Abstract: Objective:To investigate the medicative effects of medium-polar (benzene:acetone, 1:1, v/v) extract of leaves from Stevia rebaudiana (family Asteraceae) on alloxan-induced diabetic rats.Materials and Methods:Diabetes was induced in adult albino Wistar rats by intraperitoneal (i.p.) injection of alloxan (180 mg/kg). Medium-polar extract was administered orally at daily dose of 200 and 400 mg/kg body wt. basis for 10 days. The control group received normal saline (0.9%) for the same duration. Glibenclamide was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 36 publications
(33 reference statements)
0
11
0
1
Order By: Relevance
“…Malaysia does not have the optimum climate to enhance sugar cane cultivation; hence the local demand for sugar is highly dependent on sugar imports. Stevia plant is in high demand because of its potential as a non-calorific natural sweetener specifically towards individuals with body weight issues as well as diabetics (Mehta et al, 2011;Mogra & Dashora, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Malaysia does not have the optimum climate to enhance sugar cane cultivation; hence the local demand for sugar is highly dependent on sugar imports. Stevia plant is in high demand because of its potential as a non-calorific natural sweetener specifically towards individuals with body weight issues as well as diabetics (Mehta et al, 2011;Mogra & Dashora, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that CGA, stevioside and stevia extracts have anti-diabetic effects, in line with previous studies that have reported hypoglycemic effects for stevia extracts and derivatives. Previous studies have reported that stevia extracts have hypoglycemic effects in experimental animal models of DM (Assaei et al, 2016;Das et al, 2000;Misra et al, 2011). Also, Karthikesan et al (2010) demonstrated that CGA at a dose of 5 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 93%
“…Considerando lo anterior, algunos estudios han reportado que el extracto de S. rebaudiana y el esteviósido tienen efecto antihiperglucemiante, tanto en modelos animales (Jeppesen et al, 2002;Kujur et al, 2010;Lailerd et al, 2004;Misra et al, 2011; como en humanos (Curi et al, 1986;Gregersen et al, 2004), así como también efecto hipoglucemiante en ratas (Raskovic et al, 2008); por otra parte, el Rebaudiósido A, tanto en modelos animales como en humanos ha demostrado no tener efecto sobre la glucosa sanguínea.…”
Section: Efecto Antihiperglucemiante E Hipoglucemianteunclassified